Major risk factors underlying the development of metabolic syndrome in vitamin D-deficient rats - Kamel, Fatemah O.; Mahjoub, S. K.; Ahmad, M. A. A. Sattar; Jamal, Maha H.; Bakhshwin, Duaa M.; Burzangi, Abdulhadi S.; Shaker, Soad; Magadmi, Rania (Frontiers in Pharmacology, 2025)
BackgroundVitamin D is essential for calcium–phosphorus homeostasis, skeletal mineralization, and cardiovascular health. Its deficiency is associated with increased risk of metabolic syndrome and cardiovascular diseases. In this study, we aimed to investigate the relationship between vitamin D deficiency and cardiovascular metabolic syndrome while identifying underlying mechanisms.MethodologyForty-eight Wistar albino rats were divided into four groups: control, vitamin D deficient (VD-), metabolic syndrome (MetS), and combined vitamin D deficient with metabolic syndrome (VD- + MetS). VD- and VD- + MetS rats were fed a vitamin D-deficient diet with increased calcium and phosphate to prevent secondary hyperparathyroidism and to determine the direct effects of vitamin D. Metabolic syndrome was induced via 10% fructose in drinking water for 8 weeks. Evaluations included metabolic syndrome markers (hypertension, diabetes, dyslipidemia, and obesity), myocardial injury indicators (lactate dehydrogenase [LDH] and creatine kinase-MB [CK-MB]), and oxidative stress/inflammation markers (malondialdehyde [MDA] and nitric oxide [NO]). Vascular reactivity in thoracic aorta tissues, heart weight, and histopathological changes were also assessed.ResultThe results revealed that vitamin D deficiency was strongly related to each component of metabolic syndrome. Combined vitamin D deficiency and metabolic syndrome induced a highly significant increase in CK-MB, LDH, NO, and MDA levels (p < 0.05). However, there was no significant difference in CK-MB and NO levels for the (VD-) group compared to the control (p > 0.05). Heart weight was significantly increased, and a histological examination of the heart showed increased left ventricular and aortic wall thickness in the combined group (p < 0.05). Vascular response to phenylephrine was significantly increased, whereas the vascular response to acetylcholine was significantly decreased in all experimental groups (VD-, MetS, and VD- + MetS) compared to control (p < 0.05).ConclusionThe present study demonstrates that vitamin D deficiency is considered one of the major risky and predisposing factors for cardiovascular metabolic syndrome, which could affect the outcome of the disease, partly by affecting endothelial function, vascular oxidative stress, and inflammation.